(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2023)
Students require critical thinking skills, their development is constrained in Indonesia. This research, involving 21 8th-grade students in Bandung, aimed to enhance critical thinking on the human excretory system via the 5E learning cycle. This study used pre-experimental methods, researchers employed ACTA for assessment and objective tests for analysis. Data analysis using SPSS 24 revealed noteworthy improvement (p < 0.05) in critical thinking skills, confirmed by a paired t-test (sig 2-Tailed 0.000). N-Gain showed a slight enhancement of 0.24. Critical thinking levels progressed from challenged thinker to beginning thinker. According to the modest progress, the 5E model shows the potential for improving students’ critical thinking in science education